Murder at the Dinner Table: Family Narratives of Forensic Mental Health Professionals*. Issue 1 (2nd January 2019) - Regehr, Kaitlyn; Regehr, Cheryl; Glancy, Graham
Abstract: Stemming from work on emergency professionals directly affected by trauma exposure, attention has turned to the impact of work-related trauma on their families, including media and public scrutiny, trauma contagion, marital discord, and overprotective parenting. More recently, colleagues in forensic mental health are speaking anecdotally not only about the personal impact of exposure to violence, but also the impact on their families. This study uses a narrative approach to elicit stories from adult children of forensic psychiatrists to explore the extent of exposure to disturbing material, the impact of exposure, and mechanisms employed by parents to mitigate risk and exposure.